2009
DOI: 10.2527/jas.2009-1889
|View full text |Cite
|
Sign up to set email alerts
|

A survey of beef carcass quality and quantity attributes in Mexico1

Abstract: The objective of the present study was to evaluate quality and yield attributes of Mexican beef carcasses to serve as a benchmark for production in the Mexican beef cattle industry. Seven packing plants were surveyed nationwide. Carcass yield and quality traits were assessed in the cooler at approximately 24 h postmortem. Results indicated that around 90% of the beef slaughter population in Mexico has a strong Bos indicus genetic background. Moreover, 71.6% of the surveyed cattle are presented for slaughter at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 11 publications
3
11
0
11
Order By: Relevance
“…That is comparable with results of Méndez et al (2009) who reported in the survey in Mexico that 71.6% of cattle had slaughter weight in the range between 400 and 500 kg. Lower slaughter weights were presented in other study from Mexico (Martínez et al, 2006) and Costa Rica (ITCR, 2004).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…That is comparable with results of Méndez et al (2009) who reported in the survey in Mexico that 71.6% of cattle had slaughter weight in the range between 400 and 500 kg. Lower slaughter weights were presented in other study from Mexico (Martínez et al, 2006) and Costa Rica (ITCR, 2004).…”
Section: Resultssupporting
confidence: 81%
“…Also, older cows had significantly greater marbling than bulls (7.74 vs. 8.50) whereas younger cows did not. Similar results in marbling characterized as "slight, practically devoid" or "traces" have been published by Méndez et al (2009), Rubio et al (2007 and McKenna et al (2002). Significantly higher degree of marbling in cows than bulls was determined by Gondeková (2011): 7.63 vs. 8.58 andZaujec et al (2010).…”
Section: Resultssupporting
confidence: 75%
“…Samples were also taken from commercial sales points in southern Mexico (Veracruz,Veracruz (N = 12)). The samples were classified according to genetic group (GG) in Bos taurus, Bos indicus and commercial crossbreeds, on the basis of the classification used by Méndez et al (2009) who considered the phenotypic indicators of length and height of hump.…”
Section: Methodsmentioning
confidence: 99%
“…Phenotypic appearance traits and breed conformation may be used to distinguish and classify the genetic group as proposed by Casas et al (2005) and Sherbeck et al (1996) and used by Méndez et al (2009) as former methodology for this study.…”
Section: Imfmentioning
confidence: 99%
“…In all these studies pure cattle breeds were evaluated. However, in Mexico beef is derived from synthetic bovine breeds, such as Brangus, Brahman (Méndez et al, 2009) and Charolais. Synthetic breeds were developed by crossing zebu and taurine cattle and were claimed to be both highly resistant to heat like Indian cattle and highly productive like European cattle (Bicalho et al, 2006).…”
Section: Introductionmentioning
confidence: 99%